Proteins That Underlie Neoplastic Progression of Ulcerative Colitis - Brentnall, Teresa A. (2009)
Patients with ulcerative colitis (UC) have an increased risk for developing colorectal cancer. Because UC tumorigenesis is associated with genomic field defects that can extend throughout the entire colon, including the non-dysplastic mucosa; we hypothesized that the same field defect will include abnormally expressed proteins. Here we applied proteomics to study the protein expression of UC neoplastic progression. The protein profiles of colonic epithelium were compared from 1) UC patients without dysplasia (non-progressors); 2) none-dysplastic colonic tissue from UC patient with high-grade dysplasia or cancer (progressors); 3) high-grade dysplastic tissue from UC progressors and 4) normal colon. We identified protein differential expression associated with UC neoplastic progression. Proteins relating to mitochondria, oxidative activity, calcium-binding proteins were some of interesting classes of these proteins. Network analysis discovered that Sp1 and c-myc proteins may play roles in UC early and late stages of neoplastic progression, respectively. Two over-expressed proteins in the non-dysplastic tissue of UC progressors, CPS1 and S100P, were further confirmed by IHC analysis. Our study provides insight into the molecular events associated with UC neoplastic progression, which could be exploited for the development of protein biomarkers in fields of non-dysplastic mucosa that identify a patient’s risk for UC dysplasia.